2002
DOI: 10.1002/1439-2054(20020901)287:9<604::aid-mame604>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Loss of sulfide from the aqueous solution in the batchwise reaction: 1.21 g NBrSR and 100 cm 3 0.01 m Na 2 S in (1) 0.01 m NaOH, (2) 0.1 m NaOH, (3) 1 m NaOH; mole ratio active bromine/Na 2 S = 2:1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…20 The advantages of N-halamine-carrying materials include high biocidal efficacy, long-term stability, high durability, simple rechargeability and low toxicity with little environmental concern. [29][30][31][32] Previous studies demonstrated the detoxification ability of N-halamine-containing fabrics against certain carbamate and organophosphorus pesticides via oxidizing sulfide and thiophosphate groups, respectively. [25][26][27][28] Furthermore, active N-halamine structures can oxidize alcohols to ketones, sulfides to sulfoxides and sulfones, as well as cyanides to carbon dioxide and ammonium in aqueous conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 The advantages of N-halamine-carrying materials include high biocidal efficacy, long-term stability, high durability, simple rechargeability and low toxicity with little environmental concern. [29][30][31][32] Previous studies demonstrated the detoxification ability of N-halamine-containing fabrics against certain carbamate and organophosphorus pesticides via oxidizing sulfide and thiophosphate groups, respectively. [25][26][27][28] Furthermore, active N-halamine structures can oxidize alcohols to ketones, sulfides to sulfoxides and sulfones, as well as cyanides to carbon dioxide and ammonium in aqueous conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28] Furthermore, active N-halamine structures can oxidize alcohols to ketones, sulfides to sulfoxides and sulfones, as well as cyanides to carbon dioxide and ammonium in aqueous conditions. [29][30][31][32] Previous studies demonstrated the detoxification ability of N-halamine-containing fabrics against certain carbamate and organophosphorus pesticides via oxidizing sulfide and thiophosphate groups, respectively. 33,34 The successful deactivation of a sulfur mustard stimulant, chloroethyl ethyl sulfide (CEES), by N-halamine bound polystyrene beads was also reported.…”
Section: Introductionmentioning
confidence: 99%